Acute transient macular detachment after uneventful cataract surgery in a highly myopic eye - Tommaso Verdina; Tomaso Caporossi; Gian Maria Cavallini; Rodolfo Mastropasqua (American Journal of Ophthalmology Case Reports, 2021)
Purpose: We report a case of a highly myopic patient who presented a serous macular detachment at 24 hours after uncomplicated cataract surgery. Observations: Surprisingly, after six days from surgery, a reabsorption of the detachment was noticed and the macular area returned to be anatomically normal without any surgical intervention. This early postoperative complication could be caused by changes in the vitreoretinal interface and ocular fluid dynamics or to a rupture of blood-retinal barriers due to postoperative inflammation. Conclusions and importance: Our case reports on the occurrence of an early transient macular detachment after uneventful cataract surgery in a highly myopic eye. This finding suggests the importance of an OCT-based control in the immediate postoperative hours.